Language Use and Language Attitudes of Sumbawanese Speakers in Bali - Menggo, Sebastianus; Suastra, I Made (Register Journal, 2020)
This study examines the language maintenance model for a local language in another language community, specifically to examine Sumbawanese language maintenance in the Balinese community. This study encompasses 1) the Sumbawanese speakers’ competence of Sumbawanese language; 2) Sumbawanese language use patterns in the Balinese community; 3) language attitudes of Sumbawanese speakers toward their language. This study focuses on Denpasar's several locations, where most of the language interaction occurred, and data were collected through observation, interviews, and questionnaires. Those data were analyzed by using a software program, namely an excel chart data series. The research subjects were both older and younger Sumbawanese speakers. An analysis of language attitudes also considered the roles of language choice and language change in maintaining cultural diversity and ethnic identity, which will psychologically provide a feeling of assurance in personal linguistic competence. In Sumbawanese speakers, the context of communicating in Balinese society will be thoroughly considered. The findings show that speakers of Sumbawa language have good competence towards Sumbawa language, rarely use Sumbawa language, and have more positive than negative attitudes towards their language. Speakers are stimulated to maintain the frequency of language use and their positive language attitudes to be competent intercultural speakers.  Keywords: Balinese, language use, language attitude, language change, Sumbawanese